Is There Any Reason Not to Perform Standard Laparoscopic Total Mesorectal Excision? - Lakkis, Zaher; Panis, Yves (Clinics in Colon and Rectal Surgery, 2017)
The curative treatment of locally advanced rectal cancer is currently based on chemoradiotherapy and total mesorectal excision (TME). Laparoscopy has developed considerably because of obvious clinical benefits such as reduced pain and shorter hospital stay. Recently, several prospective randomized clinical trials with long-term follow-up have showed that laparoscopy is noninferior to laparotomy with the same oncologic outcomes in terms of survival and local control rate. However, laparoscopic TME remains a challenging procedure requiring a high level of expertise and a long learning curve to ensure an adequate and safe resection. The only relative contraindication of laparoscopic rectal surgery is T4 rectal cancer extended beyond the plane of TME. In this situation, it is reasonable to consider an open resection to avoid an uncomplete resection. In obese and elderly patients, laparoscopic TME also provides the same benefits as in nonobese and younger patients but may be more difficult to achieve. This review summarizes current knowledge on the place of laparoscopic TME in the treatment of rectal cancer.
Keywords: rectal cancer; TME surgery; laparoscopy